2011
DOI: 10.1002/dvdy.22606
|View full text |Cite
|
Sign up to set email alerts
|

Axonal regeneration proceeds through specific axonal fusion in transected C. elegans neurons

Abstract: Functional neuronal recovery following injury arises when severed axons reconnect with their targets. In Caenorhabditis elegans following laser-induced axotomy, the axon still attached to the cell body is able to regrow and reconnect with its separated distal fragment. Here we show that reconnection of separated axon fragments during regeneration of C. elegans mechanosensory neurons occurs through a mechanism of axonal fusion, which prevents Wallerian degeneration of the distal fragment. Through electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 41 publications
2
95
0
Order By: Relevance
“…In some cases, the regenerating axon can fuse with the distal segment, preventing it from degeneration. 1 Based on studies in a variety of organisms, it was found that although the capacity of neuronal regeneration should be universal, in C. elegans as a genetic model to identify novel cellular and molecular mechanisms underlying nervous system regeneration Caenorhabditis elegans has emerged as a powerful model for studying axon regeneration since the invention of the femtosecond laser system opens up the possibilities for high throughput genetic screens to identify novel genes involved in regulating axon regeneration. 2 In this review, we first discuss the general view about nerve regeneration and the advantages of using C. elegans as a model system to study axon regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the regenerating axon can fuse with the distal segment, preventing it from degeneration. 1 Based on studies in a variety of organisms, it was found that although the capacity of neuronal regeneration should be universal, in C. elegans as a genetic model to identify novel cellular and molecular mechanisms underlying nervous system regeneration Caenorhabditis elegans has emerged as a powerful model for studying axon regeneration since the invention of the femtosecond laser system opens up the possibilities for high throughput genetic screens to identify novel genes involved in regulating axon regeneration. 2 In this review, we first discuss the general view about nerve regeneration and the advantages of using C. elegans as a model system to study axon regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that the process of axonal fusion might resemble that of apoptosis 7 , in which the dying cell exposes "eat-me" signals that mediate recognition and engulfment by surrounding phagocytes. During apoptosis, plasma membrane phospholipid asymmetry is lost, causing phosphatidylserine (PS), which is normally restricted to the cytoplasmic leaflet, to be externalized to the exoplasmic leaflet where it enables recognition by phagocytic cells [8][9][10][11] .…”
Section: Axonal Fusion During Regeneration Requires Conserved Componentsmentioning
confidence: 99%
“…While axon fusion is conserved across a range of species [1][2][3][4][5][6][7] , EFF-1 is not 26 . In order to identify other conserved components required for this process, we undertook a candidate screen on molecules previously identified to mediate biological events that we predicted might share open arrowheads show fusion site; scale bar 25 μm.…”
Section: Axonal Fusion During Regeneration Requires Conserved Componentsmentioning
confidence: 99%
See 2 more Smart Citations